Density measurements of compressed dipropyl, dibutul, bis (2-ethylhexyl) adipates from (293 to 373K) at pressures up to about 68MPa - Diogo, João C. F. (2015)
The article reports density measurements of dipropyl (DPA), dibutyl (DBA) and bis(2-ethylhexyl) (DEHA) adipates, using a vibrating U-tube densimeter, model DMA HP, from Anton Paar GmbH. The measurements were performed in the temperature range (293 to 373) K and at pressures up to about 68 MPa, except for DPA for which the upper limits were 363 K and 65 MPa, respectively. The density data for each liquid was correlated with the temperature and pressure using a modified Tait equation. The expanded uncertainty of the present density results is estimated as 0.2% at a 95% confidence level. No literature density data at pressures higher than 0.1 MPa could be found. DEHA literature data at atmospheric pressure agree with the correlation of the present measurements, in the corresponding temperature range, within +/- 0.11%. The isothermal compressibility and the isobaric thermal expansion were calculated by differentiation of the modified Tait correlation equation. These two parameters were also calculated for dimethyl adipate (DMA), from density data reported in a previous work. The uncertainties of isothermal compressibility and the isobaric thermal expansion are estimated to be less than +/- 1.7% and +/- 1.1%, respectively, at a 95% confidence level. Literature data of isothermal compressibility and isobaric thermal expansivity for DMA have an agreement within +/- 1% and +/- 2.4%, respectively, with results calculated in this work. (C) 2014 Elsevier B.V. All rights reserved.